Concentração de microplásticos em cérebro, fígado, rim e músculo, de um peixe iliófago no Rio dos Sinos - Silveira, Daniela da Cunha (Universidade do Vale do Rio dos Sinos, 2025)
This thesis investigated contamination by microplastics (MPs), a xenobiotic present in the environment, in a fish species found in the Sinos River, RS. The main objective was to analyze MP contamination in the brain, liver, kidney, and muscle tissues of the species Cyphocharax voga. The study tested the hypothesis that there are significant differences in the concentration of plastic particles among the organs of 54 individuals, consisting of 25 males and 29 females. For the identification of MPs, the chemical staining technique with Nile Red dye was used, followed by fluorescence microscopy analysis.The results indicated a higher mean concentration of MPs/g in the brain (192 ± 124 MP/g), followed by the liver (65 ± 37 MP/g), kidney (47 ± 25 MP/g), and muscle tissue (39 ± 24 MP/g). The analysis also revealed significant differences in MP contamination between sexes in the brain and liver. A significant mean correlation was observed between the liver and kidney (p = 0.004; r = -0.481), as well as between the brain and kidney (p = 0.012; r = -0.424). Furthermore, the results evidenced the presence of MPs in all sampled tissues and reinforced the brain as a sensitive organ for biomonitoring. MP fragments were the most abundant form, occurring in significantly higher amounts compared to foams/films, spheres, and fibers.Although no correlation was found between MP concentration and the condition factor (Kn), one of the secondary objectives of this study, the research results confirmed the initial hypothesis, highlighting the existence of differences in MP contamination in the brain, liver, kidney, and muscle tissues of aquatic organisms, and underscoring the need for continuous monitoring of MP pollution in humanimpacted environments.This work provides important knowledge on the occurrence of MPs in freshwater fish, which may be useful for future studies on the hazards of these pollutants to the health of aquatic environments, as they can be considered a model for other vertebrates, including humans.
Keywords: Microplásticos; Ecotoxicologia; Fator de condição; Diferença sexual; Microplastics; Ecotoxicology; Condition factor; Sexual difference; ACCNPQ::Ciências Biológicas::Biologia Geral